Pharmacological treatment of asthma in a cohort of adults during a 20-year period: results from the European Community Respiratory Health Survey I, II and III. Issue 1 (1st February 2019) - Janson, Christer; Accordini, Simone; Cazzoletti, Lucia; Cerveri, Isa; Chanoine, Sebastien; Corsico, Angelo; Ferreira, Diogenes Seraphim; Garcia-Aymerich, Judith; Gislason, David; Nielsen, Rune; Johannessen, Ane; Jogi, Rain; et al.
Asthma often remains uncontrolled, despite the fact that the pharmacological treatment has undergone large changes. We studied changes in the treatment of asthma over a 20-year period and identified factors associated with the regular use of inhaled corticosteroid (ICS) treatment. Changes in the use of medication were determined in 4617 randomly selected subjects, while changes in adults with persistent asthma were analysed in 369 participants. The study compares data from three surveys in 24 centres in 11 countries. The use of ICSs increased from 1.7% to 5.9% in the general population and the regular use of ICSs increased from 19% to 34% among persistent asthmatic subjects. The proportion of asthmatic subjects reporting asthma attacks in the last 12 months decreased, while the proportion that had seen a doctor in the last 12 months remained unchanged (42%). Subjects with asthma who had experienced attacks or had seen a doctor were more likely to use ICSs on a regular basis. Although ICS use has increased, only one-third of subjects with persistent asthma take ICSs on a regular basis. Less than half had seen a doctor during the last year. This indicates that underuse of ICSs and lack of regular healthcare contacts remains a problem in the management of asthma. Despite increased ICS use, only 34% of subjects with persistent asthma take ICSs on a regular basis; <50% have seen a doctor in the last year. Underuse of ICSs and lack of regular healthcare contacts remains a problem in asthma. http://ow.ly/GUZ630mZkVN